Sediment Transport Mechanism and Provenance of Unconsolidated Sediments in Opak River Channel, Yogyakarta, Indonesia - Widada, Sugeng; Putra, Roy Andika; Prahastomi, Mochammad; Rizky, Aga (Jurnal Ilmiah Geologi PANGEA, 2024)
This study focuses on the Opak River, which crosses administratively through two regencies, Sleman and Bantul. This research aims to reveal the sedimentation mechanism and provenance of Opak River sediment based on textural and sedimentary composition. Sediment samples were collected from ten points along the river channel, spanning from upstream to downstream. Granulometric and grain morphology analysis were conducted which the followed by QFL analysis wherein the presence of light detrital minerals (quartz, feldspar, lithic) was observed. The sediment texture of Opak River Channel generally consists of coarse-grained sand, poorly sorted, with varying degrees of roundness and sphericity, which are angular to sub-rounded and intermediate to sub-equant, respectively. Opak River sediment predominantly comprises Feldspar (20-48%), Quartz (4-17,9%) and Lithic (13,5-19,6%) which implies arkose-lithic arkose type. The sedimentation process in Opak River is mainly driven by the traction process, which is indicated by a 48-79% traction fraction on the probability log curve. Based on QFL analysis, it is inferred that the Opak River sediment originated tectonically derived from a magmatic arc setting, specifically a transitional arc subtype. The primary sediment source could have been derived from Mount Merapi with a potentially strong influence by the Oyo River, especially in the downstream of Opak River.